The Scientific Calling of the Church: Herman Bavinck's Exhortation for the Churches in Mainland China - Xu, Ximian (Studies in world christianity, 2021)
Herman Bavinck (1854–1921) describes the twofold scientific calling of the Church. First, the Church needs to read the historic Reformed confessions contextually and distill the Reformed principles to meet its contemporary needs. Second, the Church should pursue a scientific (wetenschappelijke) life, particularly in the university. Bavinck's twofold theological insight can be applied to the churches in mainland China. The first reminds Chinese Reformed churches of the necessity of composing a Sino-Reformed confession. The second insight exhorts churches to develop scientific life publicly. In this sense, the scientific calling of the church, which Bavinck envisaged more than a century before, can be fulfilled in the twenty-first-century mainland China. 1